LINGUISTIC GLOBALIZATION AND THE CHALLENGES OF LANGUAGE DIVERSITY: GLOBALIZATION, LANGUAGE SHIFT, AND THE PRESERVATION OF MINORITY LANGUAGES - Nematova Shakhlokhon Dilshodbek kizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
The article analyzes the relationship between globalization and linguistic diversity, focusing on how global economic and cultural integration affects language use and policy. It discusses the increasing dominance of global languages and the risks this trend poses to minority and indigenous languages. Special attention is given to multilingual education, language planning, and strategies for preserving linguistic diversity in a globalized world.